Exploring the role of epistemic benefit and responsible tourist behaviour in the selection of local wine by tourists - Edgar J. Sabina del Castillo; Ricardo J. Díaz Armas; Desiderio Gutiérrez Taño (Agricultural Economics (AGRICECON), 2025)
The consumption of local wine at tourist destinations plays a fundamental role in creating authentic experiences. However, there is very little research that has looked in depth into the factors that influence tourists' consumption of this product, especially in relation to epistemic benefits and responsible tourist behaviour. This study proposes a theoretical model based on the Theory of Planned Behaviour (TPB). We conducted a survey involving 619 travellers who regularly consume wine when visiting Tenerife (Canary Islands, Spain). The results show that epistemic benefit and responsible tourist behaviour have a positive relationship with attitudes toward local wine consumption, subjective norms, and perceived behavioural control. Furthermore, the relationships proposed by the TPB are confirmed, except for the relationship between subjective norms and behavioural intention. These findings provide new knowledge on local wine consumption by tourists which will help to develop strategies to encourage its consumption in tourist destinations.